Repetition In Educational Psychology: A Study Of The Qur’an Surah Ar-Rahman - Harianto, Eko; Muhammad, Muhammad; Anis, Muhammad; Fauzan, Aris (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
Learning is a process of increasing knowledge. However, limited memory makes it easy for students to forget the material given by the teacher. Therefore, it is necessary to repeat the material to strengthen memory. The subject matter is repeated to recall and increase the understanding of the material that has been learned. The subject matter is repeated to recall and increase the understanding of the material that has been learned. Given the limitations of human memory that are easy to forget, the repetition of material is considered important to strengthen memory, as expressed in Surah Ar-Rahman. This study aims to describe the value of repetition in educational psychology. This research is a literature study with a qualitative approach, using maudhu'i (thematic) interpretation to analyse Surah Ar-Rahman. Repetition can increase a person's attention in the learning process, where generally individuals tend to imitate what others say. Through repetition, students will have a good and deep understanding.